We carry their bones : the search for justice at the Dozier School for Boys - Kimmerle, Erin H. (William Morrow, an imprint of HarperCollinsPublishers, 2022)
Recounts the story of the Dozier School, a Florida reform school shut down in 2011 due to reports of cruelty, abuse, and mysterious deaths, and the efforts of the author, a leading forensic anthropologist, to locate and exhume the graves of the boys buried there in order to reunite them with their families.